Biobeat monitor utilization in various healthcare settings: A systematic review - Yifan Zhang; Jill Querney; Yamini Subramani; Kendra Naismith; Priyanka Singh; Lee-Anne Fochesato; Nida Fatima; Natasha Wood; Richard Malthaner; Mahesh Nagappa (Digital Health)
Background Ensuring accurate and continuous monitoring of patients’ physiological parameters is paramount for evaluating their health status and guiding clinical decision-making. Technological advancements have the potential to significantly improve patient care and outcomes by offering a seamless continuum of healthcare experiences. Biobeat Technologies Ltd has pioneered a non−invasive wearable approach to acquiring advanced hemodynamic parameters, employing devices such as the BB−613WP wrist monitor and the BB−613P chest patch. Biobeat devices have been applicable across many clinical settings, as substantiated by a growing body of research. This systematic review endeavours to comprehensively consolidate the evidence regarding using Biobeat monitors across various clinical scenarios. Methods From 2016 to 2024, a thorough literature search was conducted across multiple databases. The inclusion criteria for selected studies comprised adult patients aged 18 years or older in any healthcare setting, employing Biobeat monitoring devices (wrist monitors and/or chest patches), reporting at least one outcome or finding, and presenting fully published original research studies, including randomized controlled trials and prospective or retrospective cohort studies. The quality and risk of bias assessment for the studies was performed using the Newcastle−Ottawa scale and COSMIN scoring system. Results Among 27 studies identified, 15 met the inclusion criteria, involving 4248 patients. These included 14 prospective observational studies and one retrospective cohort study; no randomized control trials were identified. Notably, eight studies were conducted in ambulatory settings, with 1 study focusing on patients undergoing labor and delivery. Additionally, three studies were carried out in general inpatient wards, 1 in a medical ICU and another in a cardiac surgery ICU (CSICU). Furthermore, 1 study presented results from 3 separate investigations— 2 in ambulatory settings and 1 in the CSICU. Across all studies, Biobeat devices were consistently utilized, with each study reporting positive outcomes associated with their use. Conclusion This systematic review demonstrates that Biobeat's non-invasive wearable devices have been effectively utilized across various clinical settings, consistently contributing to positive patient outcomes. The versatility and reliability of these devices highlight their potential to enhance patient care and support clinical decision-making, warranting further research to explore their broader applications.